Chasing freedom the Philippines' long journey to democratic ambivalence - Webb, Adele (Quezon City Ateneo de Manila University Press, 2021)
"How did Rodrigo Duterte earn the support of large segments of the Philippine middle class, despite imposing arbitrary rule and offering little tolerance for dissent? Has the Filipino middle class, heroes of the 1986 People Power Revolution, given up on democracy?

Chasing Freedom tells the story of the love/hate relationship of the Philippine middle class with democratic politics. It illuminates the historical roots and contingency of the Philippine middle-class’s reticence about democracy and makes visible the forms of power that have shaped and constrained middle-class imaginings of democracy and representations of themselves as political subjects. Drawing on historical archival work, discourse analysis, and fieldwork interviews, the chapters trace the attitudes of the Filipino middle class from the time of American colonization in 1898 to the 2016 election of strongman Rodrigo Duterte. The argument is that democracy has been, and continues to be, lived in a deeply ambivalent way. The simultaneous saying of “yes” and “no” to democracy by citizens is one of the defining features of the Philippines’ democratic journey. The prime source of this ambivalence, the book argues, is the Janus face of America’s “democratic imperialism”, and the deprecation inherent in the project of “democratic tutelage.”

According to Webb, the Philippines is a bellwether case of what she calls democratic ambivalence. In an age when disenchantment with democracy is on the rise, it provides lessons of global importance. The book’s empirical findings support a striking conclusion: since ambivalence is not simply a “pathology” of democracy, but one of its persistent features, the dynamics of ambivalence need to be at the heart of descriptive and normative accounts of how democracy works."--Back cover.
"First published in 2021 by Sussex Academic Press."--Verso of the title page.
Revision of the author's thesis (doctoral)--University of Sydney, 2018.
Includes bibliographical references and index.
Keywords: Democracy -- Philippines -- Public opinion; Middle class -- Philippines -- Attitudes; Philippines -- Politics and government